The (Structural) Gravity of Epidemics - Alejandro Cu\~nat; Robert Zymek (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Epidemiological models assume gravity-like interactions of individuals across space without microfoundations. We combine a simple epidemiological frame-work with a dynamic model of individual location choice. The model predicts that flows of people across space obey a structural gravity equation. By means of an application to data from Great Britain we show that our structural-gravity framework: provides a rationale for quarantines; offers a clear mapping from observed geography to the spread of a disease; and makes it possible to evaluate the welfare impact of (expected and unexpected) mobility restrictions in the face of a deadly epidemic.
Keywords: E65; F14; F17; J61; R23; 330; epidemics; Covid-19; gravity; regional mobility